2002
DOI: 10.1109/jqe.2002.802111
|View full text |Cite
|
Sign up to set email alerts
|

High-power passively mode-locked semiconductor lasers

Abstract: We have developed optically pumped passively mode-locked vertical-external-cavity surface-emitting lasers. We achieved as much as 950 mW of mode-locked average power in chirped 15-ps pulses, or 530 mW in 3.9-ps pulses with moderate chirp. Both lasers operate at a repetition rate of 6 GHz and have a diffraction-limited output beam near 950 nm. In continuous-wave operation, we demonstrate an average output power as high as 2.2 W. Device designs with a low thermal impedance and a smooth gain spectrum are the key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 167 publications
(76 citation statements)
references
References 26 publications
2
74
0
Order By: Relevance
“…6a and 7. Thus, a moderately doped thick FIGURE 7 Carrier distribution along the radial axis in the active region. The device exhibits a bottom contact radius r 3 = 25 µm, an aperture radius r 2 = 50 µm, and a bottom p-DBR.…”
Section: Current-spreading Layer or Cap Layermentioning
confidence: 99%
See 1 more Smart Citation
“…6a and 7. Thus, a moderately doped thick FIGURE 7 Carrier distribution along the radial axis in the active region. The device exhibits a bottom contact radius r 3 = 25 µm, an aperture radius r 2 = 50 µm, and a bottom p-DBR.…”
Section: Current-spreading Layer or Cap Layermentioning
confidence: 99%
“…Passive mode locking of an optically pumped VECSEL has been demonstrated with a semiconductor saturable absorber mirror (SESAM) [5] in a folded external cavity. After the first passively mode locked VECSEL was demonstrated in the year 2000 [6], the milestone of nearly 1 W average output power was achieved in 2002 with improved thermal management [7]. The pulses in the early experiments were often strongly chirped, but mode-locking dynamics in VECSELs revealed that a soliton-like pulse-shaping mechanism in the positive-dispersion regime can help to generate short pulses with low chirp.…”
mentioning
confidence: 99%
“…We did not optimize thermal management because this experiment was a proof-of-principle for modelocking a QD-VECSEL. Thus the 450 µm thick GaAs substrate has not been removed, and the average power is limited by thermal heat sinking [4]. The advantage of this structure is that almost no additional processing is required before the device can be used in the laser cavity.…”
Section: Resultsmentioning
confidence: 99%
“…For our experiment, the QD-VECSEL structure was directly soldered onto a heat sink, and no further steps were taken towards improved thermal management [4]. During modelocked laser operation, the heat sink temperature was set to −20 • C.…”
Section: Laser Cavity Qd-vecsel Gain Structure and Sesammentioning
confidence: 99%
“…The thermal conductivity of the ternary alloy can be as low as 11 W m −1 K −1 for compositions close to Al 0.5 Ga 0.5 As. A similar approach has enabled Häring et al [8] to demonstrate 2.2 W in cw operation in a near-diffraction-limited beam. An effective technique that extracts heat directly from the active region, rather than through the DBR, was introduced by Alford et al [9], who put an uncoated sapphire window incontact with the front surface of a VECSEL gain element, where it acted as a heat-spreading plate.…”
Section: High Power Operationmentioning
confidence: 96%